1982
DOI: 10.1021/es00106a012
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography/mass spectrometry identification of organic volatiles contributing to rendering odors

Abstract: chemical Oxidants and Precursors"; EPA-450/2-77-021a, Nov 1977.(2) U.S. EPA, "Procedures for Quantifying Relationships between Photochemical Oxidants and Precursors: Supporting Documentation"; EPA-450/2-77-021b, Feb 1978.(3) U.S. EPA, "Guideline for Use of City-Specific EKMA in Preparing Ozone SIPs"; EPA-450/4-80-027 Mar 1981. (4) Trijonis, J.; Mortimer, S. "Analysis of Historical Ozone Trends in the Los Angeles Region Using the EKMA Iso-pleth Model"; report prepared for EPA by Santa Fe Research Corp., Mar 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…7,11,12 Compounds not observed in our work but reported by others include the higher molecular weight hydrocarbons and aldehydes 7,11 and volatile fatty acids. 11 Methods have been developed for detecting the higher-molecular-weight compounds, heptane and benzaldehyde, but these compounds were not routinely detected during sampling. Detection of some higher-molecularweight compounds, as well as volatile fatty acids (i.e., decane, dodecane, octanal, tridecane, and tetradecane) may not have been possible at the low column temperatures used in our experimental protocols.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…7,11,12 Compounds not observed in our work but reported by others include the higher molecular weight hydrocarbons and aldehydes 7,11 and volatile fatty acids. 11 Methods have been developed for detecting the higher-molecular-weight compounds, heptane and benzaldehyde, but these compounds were not routinely detected during sampling. Detection of some higher-molecularweight compounds, as well as volatile fatty acids (i.e., decane, dodecane, octanal, tridecane, and tetradecane) may not have been possible at the low column temperatures used in our experimental protocols.…”
Section: Discussionmentioning
confidence: 49%
“…3,11 The major compounds identified in this study, methanethiol, 2-methylbutanal, 3-methylbutanal, hexanal, heptanal, propanal, isobutanal, dimethyl disulfide, and octane, have previously been reported but rarely quantified. 7,11,12 Compounds not observed in our work but reported by others include the higher molecular weight hydrocarbons and aldehydes 7,11 and volatile fatty acids. 11 Methods have been developed for detecting the higher-molecular-weight compounds, heptane and benzaldehyde, but these compounds were not routinely detected during sampling.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These are popularly associated with the unpleasant odours generated during the cooking process in rendering plants. They are largely attributable to the presence of VOSCs (volatile organic sulfidic compounds), amines, acids, alcohols and aldehydes (Chélu and Nominé, 1984;Prokop and Bohn, 1985;van Langenhove, 1982). Average concentrations of 39 mg S m -3 H 2 S (peak concentrations up to 1040 mg S m -3 ) and 39 µg S m -3 MeSH (peak concentrations up to 260 mg S m -3 ) with ranges 5.2-15.6 mg S m -3 for DMDS and 0.78-7.8 mg S m -3 for DMTS,…”
Section: Food Processing and Wastementioning
confidence: 99%
“…Van Langenhove et al (1982) reported that 110 volatile compounds can be identified in rendering odours, but of those, only 26 contribute most notably to malodorous rendering plant emissions. Those 26 offensive agents include 10 different aldehydes, eight different carboxylic acids, five different sulphur-containing compounds.…”
mentioning
confidence: 99%